Correlation between inflammatory marker and lipid metabolism in patients with uterine leiomyomas - Duan, Yanan; Guo, Lizhu; Peng, Yiqing; Shi, Xiuling; Zhao, Ying; Liu, Kunyan; Zhou, Runsheng; Fu, Junjie; Peng, Cunxu (Frontiers in Medicine, 2023)
Obesity is a risk factor for the development of uterine leiomyoma (UL), and the inflammatory response plays a key role in the pathogenesis of UL. Our objective was to assess whether there was an independent relationship between inflammatory markers and triglycerides (TG) in patients with UL. 1,477 UL participants who were hospitalized at the Jining Medical University between January 2016 and December 2022 were included in this cross-sectional study. The independent and dependent variables measured at baseline were inflammatory markers and TG levels, respectively. The covariates were age, body mass index (BMI), UL and menstrual status. Based on the number of fibroids, the study population was divided into Single-group and Multiple-group. Univariate and multiple regression analyses and stratified analyses revealed significant positive correlations between neutrophil-lymphocyte ratio and systemic immune inflammation index and TG, and significant negative correlations between monocyte-lymphocyte ratio and TG. The findings show a significant correlation between the inflammatory response and lipid metabolism levels in UL patients. This provides direction for further research into the pathophysiology of UL and also helps to formulate hypotheses for predictive models of UL.